Security and Cryptography for Networks 8th International Conference, SCN 2012, Amalfi, Italy, September 5-7, 2012. Proceedings - Visconti, Ivan.; Prisco, Roberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 8th International Conference on Security and Cryptography, SCN 2012, held in Amalfi, Italy, in September 2012. The 31 papers presented in this volume were carefully reviewed and selected from 72 submissions. They are organized in topical sections on cryptography from lattices; signature schemes; encryption schemes; efficient two-party and multi-party computation; security in the UC framework; cryptanalysis; efficient constructions; and protocols and combiners.
Deterministic Public Key Encryption and Identity-Based Encryption from Lattices in the Auxiliary-Input Setting -- Ring Switching in BGV-Style Homomorphic Encryption -- Zero-Knowledge Proofs with Low Amortized Communication from Lattice Assumptions -- Fully Anonymous Attribute Tokens from Lattices -- Efficient Structure-Preserving Signature Scheme from Standard Assumptions -- Compact Round-Optimal Partially-Blind Signatures -- History-Free Sequential Aggregate Signatures -- A New Hash-and-Sign Approach and Structure-Preserving Signatures from DLIN -- Blackbox Construction of a More Than Non-Malleable CCA1 Encryption Scheme from Plaintext Awareness -- Decentralized Dynamic Broadcast Encryption -- Time-Specific Encryption from Forward-Secure Encryption -- Efficient Two-Party and Multi-Party Computation Improved Secure Two-Party Computation via Information-Theoretic Garbled Circuits -- 5PM: Secure Pattern Matching -- Implementing AES via an Actively/Covertly Secure Dishonest-Majority MPC Protocol -- On the Centrality of Off-Line E-Cash to Concrete Partial Information Games -- Universally Composable Security with Local Adversaries -- On the Strength Comparison of the ECDLP and the IFP -- New Attacks for Knapsack Based Cryptosystems -- Multiple Differential Cryptanalysis Using LLR and (S{(B2 Statistics -- Quo Vadis Quaternion? Cryptanalysis of Rainbow over Non-commutative Rings -- Homomorphic Encryption for Multiplications and Pairing Evaluation -- Publicly Verifiable Ciphertexts -- Public-Key Encryption with Lazy Parties -- Probabilistically Correct Secure Arithmetic Computation for Modular Conversion, Zero Test, Comparison, MOD and Exponentiation -- MAC Aggregation with Message Multiplicity -- Efficiency Limitations of (SV(B-Protocols for Group Homomorphisms Revisited -- A More Efficient Computationally Sound Non-Interactive Zero-Knowledge Shuffle Argument -- Active Security in Multiparty Computation over Black-Box Groups -- Hash Combiners for Second Pre-image Resistance, Target Collision Resistance and Pre-image Resistance Have Long Output -- Human Perfectly Secure Message Transmission Protocols and Their Applications -- Oblivious Transfer with Hidden Access Control from Attribute-Based Encryption.s
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information systems; Information Systems; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing